LB01 SIX WEEKS OF SOFOSBUVIR/LEDIPASVIR TREATMENT OF ACUTE HEPATITIS C VIRUS GENOTYPE 1 MONOINFECTION: FINAL RESULTS OF THE THE GERMAN HEPNET ACUTE HCV IV STUDY. Issue 6 (1st December 2016) - Deterding, K.; Spinner, C.D.; Schott, E.; Welzel, T.M.; Gerken, G.; Klinker, H.; Spengler, U.; Wiegand, J.; Schulze zur Wiesch, J.; Pathil, A.; Cornberg, M.; Umgelter, A.; et al.
Abstract : Introduction: Early treatment of acute hepatitis C virus (HCV) infection with interferon alfa monotherapy is highly effective but is associated with frequent unfavorable side effects. There is no fully published study yet exploring the safety, efficacy and required treatment duration of interferon‐free treatment of acute hepatitis C virus monoinfection. Preliminary reports suggested that ledipasvir/sofosbuvir therapy is effective in acute hepatitis C but relapses were reported in HIV‐coinfected patients after 6 weeks of treatment. Aims & Methods: The German HepNet Acute HCV IV Study was designed as a single‐arm, prospective multicenter pilot study to evaluate the efficacy and safety of treatment with sofosbuvir plus ledipasvir (SOF/LDV) for 6 weeks without ribavirin in patients with acute genotype 1 HCV monoinfection. We here report the final 24 weeks' post‐treatment results. Results: Twenty patients were included by 10 centers (60% male, mean age 46 ± 12 years; 11 patients HCV genotype 1a, 9 patients genotype 1b). The main risk factors for HCV infection were sexual transmission ( n = 11) and medical procedures/needle stick injuries ( n = 5). Median alanine aminotransferase (ALT) and median bilirubin levels before start of antiviral treatment were 225 U/l (range 32–2716) and 13.6 µmol/l (range 5.13–111), respectively. ALT levels rapidly declined during therapy and values normalized already by treatment weeks 2 in nine patients and by week 4 in 17 patients. HCV RNA was undetectable by the Roche COBAS® AmpliPrep/COBAS® TaqMan® HCV Test v2.0 by weeks 2, 4 and 6 in eight, 13, and 20 patients, respectively. SVR‐12 was 100% and 19 patients have completed FU‐week 24 and all remained HCV‐RNA negative. One patient was lost to follow‐up at week 24 post treatment. Conclusion: Treatment for 6 weeks with LDV/SOF was well tolerated and highly effective in HCV genotype 1 monoinfected patients with acute hepatitis C. Virological response was durable after therapy for at least 24 weeks. A rapid improvement in biochemical disease activity was observed during therapy. Short‐duration treatment of acute hepatitis C could prevent the spread of HCV in high‐risk populations and may be cost‐saving as compared with treatment of chronic hepatitis C. Disclosure of Interest: Katja Deterding: Lecturer fees and travel grants from Gilead, MSD/Merck and AbbVie